2018
DOI: 10.1111/pbi.12911
|View full text |Cite
|
Sign up to set email alerts
|

Bt rice could provide ecological resistance against nontarget planthoppers

Abstract: SummaryGenetically engineered (GE) rice lines expressing Lepidoptera‐active insecticidal cry genes from the bacterium Bacillus thuringiensis (Bt) have been developed in China. Field surveys indicated that Bt rice harbours fewer rice planthoppers than non‐Bt rice although planthoppers are not sensitive to the produced Bt Cry proteins. The mechanisms underlying this phenomenon remain unknown. Here, we show that the low numbers of planthoppers on Bt rice are associated with reduced caterpillar damage. In laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…Actually, improving the efficiency of controlling pests with piercing-sucking mouthparts is still an important task. A recent study showed that less caterpillar damage in Bt rice attracts fewer planthoppers, implying possible ecological resistance against BPH (Wang et al, 2018). Whether transgenic miR-14 rice also has this kind of resistance to nontarget planthoppers requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, improving the efficiency of controlling pests with piercing-sucking mouthparts is still an important task. A recent study showed that less caterpillar damage in Bt rice attracts fewer planthoppers, implying possible ecological resistance against BPH (Wang et al, 2018). Whether transgenic miR-14 rice also has this kind of resistance to nontarget planthoppers requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This is necessary because non-Bt crop refuge has been proposed as a promising strategy for delaying the resistance development towards Bt crop (Gould, 2000;Tabashnik and Carriere, 2017). However, previous studies reported that planthoppers move from Bt to adjacent non-Bt rice fields (Chen et al 2003a;Wang et al, 2018) and that fungal diseases and non-target pests still required to be controlled with pesticides application when full yield is expected to be achieved (Wang et al, 2010). This indicates even if the cultivation of Bt rice cultivation has a great potential to reduce the use of broad-spectrum chemical insecticides (High et al, 2004), pesticides application in Bt rice is still required.…”
Section: More Noticeable Change In Soil Nematodes Community With Timementioning
confidence: 99%
“…Empirical evidence supported Bt rice can result in an evidently decreased application of pesticides, and thus benefit human health and the environment (Huang et al, 2005;Chen et al, 2011). However, the Cry1Ab/Ac protein, which was continuously produced within plant tissue of Bt-rice, could be released through root exudates during growth and persistent in the rhizosphere in paddy soils (Wang et al, 2018). Therefore, it might affect the activity, structure, diversity of soil fauna, and interactions among components of soil food webs, which in turn would influence soil fertility and plant productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The caterpillar damage induced the release of attractive volatiles for BPH, and BPH therefore preferred to feed on the non‐ Bt rice than on Bt rice plants. The less caterpillar damage‐associated resistance is considered a first example of ecological resistance of Bt plants to rice planthoppers …”
Section: Biological Control Agents Of Planthoppersmentioning
confidence: 99%
“…The less caterpillar damage-associated resistance is considered a first example of ecological resistance of Bt plants to rice planthoppers. 7 In addition to using Bacillus spp. and their gene products or insect pathogenic fungi such as Beauveria bassiana sensu lato isolate NJBb2101 as biological control agents, 8 the utilization and conservation of natural enemies and enhancement of their activities are a basic measure for biological control of planthoppers, and enhancement of the activities of natural enemies is currently one of the most attractive alternatives to biological control of planthoppers.…”
Section: Biological Control Agents Of Planthoppersmentioning
confidence: 99%